Power of Faith - 450 Years of the Heidelberg Catechism: [exhibition "Macht des Glaubens - 450 Jahre Heidelberger Katechismus" in Heidelberg und "Oranien und Religion. Ausstellung im Rahmen des 450. Jubiläums des Heidelberger Katechismus, 1563 - 2013" in Apeldoorn] - Boersma, Karla; Selderhuis, H. J. (Vandenhoeck & Ruprecht, 2013)
Consists of papers about the Heidelberg Catechism, followed by exhibition catalogs for two Heidelberg Catechism exhibits